Phase-change-free preparation method of sodium vanadium phosphate material

By using non-crystalline vanadium hydroxyoxide and other raw materials for ball milling and high-temperature calcination, the impurity generation problem caused by multiphase transformation in the preparation of sodium vanadium phosphate is solved, and the electrochemical performance of the material is improved.

CN119569018APending Publication Date: 2025-03-07SICHUAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411745656.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the existing preparation methods for sodium vanadium phosphate materials, there is fusion and conversion of multiple phases during high-temperature sintering, resulting in the generation of impurities and affecting the electrochemical properties of the material.

Method used

Mixed ball milling is performed using amorphous vanadium hydroxyoxide, phosphorus, sodium and carbon sources to form a precursor, and then calcined at a high temperature of 600-1000°C for 6 to 10 hours to avoid multiphase transformation.

Benefits of technology

This method avoids the generation of impurities, improves the consistency and electrochemical properties of sodium vanadium phosphate material, especially in terms of rate performance and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569018A_ABST
    Figure CN119569018A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, in particular to a phase-change-free preparation method of a sodium vanadium phosphate material, which comprises the following steps: respectively weighing amorphous vanadium oxyhydroxide, a phosphorus source, a sodium source and a carbon source, mixing, and carrying out ball milling for 1-7 hours to obtain a precursor; and calcining the precursor at 600-1000 DEG C for 6-10 hours, and cooling to obtain the Na3V2 (PO4) 3 material. Crystalline vanadium oxide in the prior art is replaced by amorphous hydroxyl vanadium oxide, and all the raw materials react in the subsequent ball-milling and mixing process, so that fusion and conversion of multiple phases are avoided in the subsequent high-temperature sintering process, generation of impure phases is avoided, and the consistency and electrochemical performance of the sodium vanadium phosphate material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery materials, and in particular to a method for preparing a sodium vanadium phosphate material without phase change. Background Art

[0002] The excessive use of fossil fuels has led to serious environmental pollution, prompting people to turn to renewable energy sources such as solar energy, wind energy, and tidal energy. However, due to the intermittent characteristics of these energy sources, effective energy storage systems (ESSs) are needed to ensure the continuity and stability of power supply. Among the many energy storage technologies, secondary batteries are favored for their flexibility, efficient energy conversion, and simple maintenance. In particular, sodium-ion batteries are considered to be more suitable as a large-scale energy storage solution than lithium-ion batteries due to their abundant sodium resources. Polyanionic materials, such as NASICON (fast ion conductor of sodium) compounds, have become a research hotspot for sodium-ion battery cathode materials due to their high operating voltage, stable structure, and excellent safety. Recent studies on sodium-ion batteries (SIBs) have confirmed that Na3V2(PO4)3 (abbreviated as: NVP) as a positive electrode material has a theoretical capacity of approximately 117 mAhg-1 and an operating voltage of approximately 3.3 V, exhibiting excellent rate performance and supporting high-power rapid charging and discharging. It also shows advantages in cycle stability and safety. Therefore, the NVP positive electrode is very suitable for rapid and frequent charging and discharging during peak load transfer in grid-scale energy storage systems.

[0003] The phase composition of NVP is crucial to its electrochemical performance. Existing technologies mostly use commercial vanadium pentoxide, ammonium metavanadate, sodium metavanadate and other crystalline products as raw materials. Therefore, there are multiple fusion and conversion between phases during the high-temperature sintering process. Multiphase transformation will lead to the formation of impurities, affecting the purity and consistency of the material. Traditional solid-phase methods often lead to multiphase transformations, and it is difficult to ensure purity and batch stability. Although precise temperature and atmosphere control technologies help to form pure phases, they increase costs, especially in large-scale production where temperature and atmosphere are not easy to be uniform. Therefore, the challenge in producing NVP is to avoid multiphase transformations during its high-temperature sintering process. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a phase-change-free preparation method of sodium vanadium phosphate material, so as to at least solve the problem that the multiphase transformation during high-temperature calcination in the existing NVP preparation method leads to impurity formation and affects the electrochemical properties of NVP.

[0005] The present invention solves the above technical problems by the following technical means:

[0006] The embodiment of the present invention provides a method for preparing a sodium vanadium phosphate material without phase change, comprising the following steps:

[0007] Weighing non-crystalline vanadium oxyhydroxide, phosphorus source, sodium source and carbon source respectively, mixing and ball milling for 1 to 7 hours to obtain a precursor;

[0008] The precursor is calcined at 600-1000°C for 6-10 hours, cooled, and Na3V2(PO4)3 material is obtained.

[0009] In some embodiments, the preparation method of the non-crystalline vanadium oxyhydroxide is as follows:

[0010] Take the vanadium-containing solution, add sodium hydroxide solution under stirring to adjust the pH value to 4.5-5, control the temperature to 40-90°C for precipitation reaction for 1-10 hours, filter to obtain a solid product, wash the solid product with deionized water and ethanol, dry and crush to obtain VO(OH)2 powder.

[0011] In some embodiments, the molar ratio of vanadium to sodium hydroxide in the vanadium-containing solution is 1:2.

[0012] In some embodiments, the vanadium-containing solution is an aqueous solution with a concentration of 5 to 10 g / L of a vanadium-containing compound, and the vanadium-containing compound is at least one of ammonium metavanadate, sodium metavanadate, vanadium pentoxide, vanadium trioxide, and vanadium dioxide.

[0013] In some embodiments, the concentration of the sodium hydroxide solution is 0.3-0.6 mol / L.

[0014] In some embodiments, the molar ratio of the vanadium oxyhydroxide, the phosphorus source, and the sodium source is 2:3:3.

[0015] In some embodiments, the mass ratio of the vanadium oxyhydroxide to the carbon source is 1:(0.2-0.5).

[0016] In some embodiments, the phosphorus source is at least one of diammonium dihydrogen phosphate, sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, diammonium hydrogen phosphate, and phosphoric acid.

[0017] In some embodiments, the sodium source is at least one of sodium hydroxide, sodium carbonate, sodium oxalate, sodium dihydrogen phosphate, sodium acetate, and sodium citrate.

[0018] In some embodiments, the carbon source is at least one of glucose, sucrose, cellulose, starch, carbon nanotubes, acetylene black, and graphite.

[0019] The present invention discloses a method for preparing sodium vanadium phosphate material without phase change, wherein the crystalline vanadium oxide in the prior art is replaced with amorphous vanadium oxyhydroxide, and the raw materials react in the subsequent ball milling mixing process, thereby avoiding the fusion and conversion of multiple phases in the subsequent high-temperature sintering process, avoiding the generation of impurities, and improving the consistency and electrochemical performance of the sodium vanadium phosphate material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is a schematic diagram of a phase-change-free path in the preparation method of the present invention;

[0021] Figure 2 is the XRD pattern of the transformation of the precursor to the Na3V2(PO4)3 material during the calcination process in Example 1;

[0022] Figure 3 is the XRD diagram of the Na3V2(PO4)3 material prepared in Example 1 and Comparative Example 1;

[0023] Figure 4 The rate performance diagrams of the Na3V2(PO4)3 materials prepared in Example 1 and Comparative Example 1 respectively applied to batteries;

[0024] Figure 5 These are the cycle stability diagrams of the Na3V2(PO4)3 materials prepared in Example 1 and Comparative Example 1 when used in batteries respectively. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0026] In the embodiments of the present application, words such as "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the embodiments of the present application should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.

[0027] In the existing preparation methods of sodium vanadium phosphate materials, there are multiple phases fusion and transformation during high-temperature calcination, and impurities are generated, which affects the electrochemical performance of NVP. For this reason, please refer to Figure 1 The present invention proposes a phase-change-free preparation method of sodium vanadium phosphate material, in which the crystalline vanadium oxide in the prior art is replaced with amorphous vanadium oxyhydroxide, and the raw materials react in the subsequent ball milling mixing process, thereby avoiding the fusion and conversion of multiple phases in the subsequent high-temperature sintering process, avoiding the generation of impure phases, and improving the consistency and electrochemical properties of the sodium vanadium phosphate material.

[0028] A method for preparing a sodium vanadium phosphate material without phase change comprises the following steps:

[0029] Weighing non-crystalline vanadium oxyhydroxide, phosphorus source, sodium source and carbon source respectively, mixing and ball milling for 1 to 7 hours to obtain a precursor;

[0030] The precursor is calcined at 600-1000°C for 6-10 hours, cooled, and Na3V2(PO4)3 material is obtained.

[0031] The preparation method of non-crystalline vanadium hydroxide oxide is as follows: take a vanadium-containing solution, add sodium hydroxide solution under stirring to adjust the pH value to 4.5-5, control the temperature to 40-90°C for precipitation reaction for 1-10 hours, filter to obtain a solid product, wash the solid product with deionized water and ethanol, dry, and crush to obtain VO(OH)2 powder. The molar ratio of vanadium to sodium hydroxide in the vanadium-containing solution is 1:2, the vanadium-containing solution is an aqueous solution with a concentration of vanadium-containing compounds of 5-10 g / L, the vanadium-containing compound is at least one of ammonium metavanadate, sodium metavanadate, vanadium pentoxide, vanadium trioxide, and vanadium dioxide, and the concentration of the sodium hydroxide solution is 0.3-0.6 mol / L.

[0032] The molar ratio of vanadium oxyhydroxide, phosphorus source and sodium source is 2:3:3, the mass ratio of vanadium oxyhydroxide and carbon source is 1:(0.2-0.5), the phosphorus source is at least one of ammonium dihydrogen phosphate, sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, diammonium hydrogen phosphate and phosphoric acid, the sodium source is at least one of sodium hydroxide, sodium carbonate, sodium oxalate, sodium dihydrogen phosphate, sodium acetate and sodium citrate, and the carbon source is at least one of glucose, sucrose, cellulose, starch, carbon nanotubes, acetylene black and graphite.

[0033] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0034] Example 1

[0035] The phase-change-free preparation method of the sodium vanadium phosphate material of this embodiment is as follows:

[0036] (1) Preparation of vanadium oxyhydroxide

[0037] According to the molar ratio of vanadium to sodium hydroxide of 1:2, vanadium pentoxide was weighed and added to deionized water, and ultrasonic dispersion was performed to obtain a vanadium-containing solution with a concentration of 8 g / L. Polyvinyl pyrrolidone was added as a structure-directing agent, and the amount of polyvinyl pyrrolidone was 0.001 times the mass of vanadium pentoxide. Then, 0.5 mol / L sodium hydroxide solution was added dropwise under continuous stirring to adjust the pH value to 4.5. The temperature was controlled at 50°C for precipitation reaction for 5 hours. When dark green flocculent precipitates were produced in the reaction liquid, the solid product was filtered to obtain the solid product. The solid product was washed with deionized water and ethanol, dried at 75°C, and crushed to obtain VO(OH)2 powder.

[0038] (2) Preparation of precursor

[0039] Sodium dihydrogen phosphate was used as both the phosphorus source and the sodium source, cellulose was used as the carbon source, the molar ratio of vanadium oxyhydroxide, phosphorus source and sodium source was 2:3:3, and the mass ratio of vanadium oxyhydroxide and carbon source was 1:0.3. Amorphous vanadium oxyhydroxide, phosphorus source, sodium source and carbon source were weighed separately and mixed, and ball milled at 500 r / min for 5 h to obtain a precursor.

[0040] (3) Calcination

[0041] The precursor was calcined at 650°C for 8 hours and cooled to obtain Na3V2(PO4)3 material.

[0042] Example 2

[0043] The difference between this embodiment and embodiment 1 is that the calcination temperature of the precursor is 600° C., and the rest is the same as embodiment 1.

[0044] Example 3

[0045] The difference between this embodiment and embodiment 1 is that the calcination temperature of the precursor is 650° C., and the rest is the same as embodiment 1.

[0046] Example 4

[0047] The difference between this embodiment and embodiment 1 is that the calcination temperature of the precursor is 700° C., and the rest is the same as embodiment 1.

[0048] Example 5

[0049] The difference between this embodiment and embodiment 1 is that the calcination temperature of the precursor is 900° C., and the rest is the same as embodiment 1.

[0050] Comparative Example 1

[0051] The preparation method of the sodium vanadium phosphate material of this comparative example is as follows:

[0052] (1) Preparation of precursor

[0053] Crystalline vanadium pentoxide is used as a vanadium source, sodium dihydrogen phosphate is used as both a phosphorus source and a sodium source, and cellulose is used as a carbon source. The molar ratio of the vanadium source, the phosphorus source, and the sodium source is 2:3:3, and the mass ratio of vanadium oxyhydroxide to the carbon source is 1:0.3. The vanadium source, phosphorus source, sodium source, and carbon source are respectively weighed and mixed, and the mixture is ball-milled at a speed of 500 r / min for 5 hours to obtain a precursor.

[0054] (2) Calcination

[0055] The precursor was calcined at 650°C for 8 hours and cooled to obtain Na3V2(PO4)3 material.

[0056] Example 6

[0057] The phase-change-free preparation method of the sodium vanadium phosphate material of this embodiment is as follows:

[0058] (1) Preparation of vanadium oxyhydroxide

[0059] According to the molar ratio of vanadium to sodium hydroxide of 1:2, vanadium trioxide was weighed and added to deionized water, and ultrasonic dispersion was performed to obtain a vanadium-containing solution with a concentration of 5 g / L. Polyvinyl pyrrolidone was added as a structure-directing agent, and the amount of polyvinyl pyrrolidone was 0.001 times the mass of vanadium trioxide. Then, 0.3 mol / L sodium hydroxide solution was added dropwise under continuous stirring to adjust the pH value to 4.6. The temperature was controlled at 60°C for precipitation reaction for 8 hours. Dark green flocculent precipitates were produced in the reaction liquid. The solid product was filtered to obtain the solid product. The solid product was washed with deionized water and ethanol, dried at 75°C, and crushed to obtain VO(OH)2 powder.

[0060] (2) Preparation of precursor

[0061] Phosphoric acid is used as a phosphorus source, sodium acetate is used as a sodium source, and acetylene black is used as a carbon source. The molar ratio of vanadium oxyhydroxide, phosphorus source, and sodium source is 2:3:3, and the mass ratio of vanadium oxyhydroxide and carbon source is 1:0.2. Amorphous vanadium oxyhydroxide, phosphorus source, sodium source, and carbon source are weighed separately and mixed, and ball milled at a speed of 500 r / min for 1 h to obtain a precursor.

[0062] (3) Calcination

[0063] The precursor was calcined at 650°C for 6 hours and cooled to obtain Na3V2(PO4)3 material.

[0064] Example 7

[0065] The phase-change-free preparation method of the sodium vanadium phosphate material of this embodiment is as follows:

[0066] (1) Preparation of vanadium oxyhydroxide

[0067] According to the molar ratio of vanadium to sodium hydroxide of 1:2, ammonium metavanadate was weighed and added to deionized water, and ultrasonic dispersion was performed to obtain a vanadium-containing solution with a concentration of 10 g / L. Polyvinyl pyrrolidone was added as a structure-directing agent, and the amount of polyvinyl pyrrolidone was 0.001 times the mass of vanadium pentoxide. Then, 0.6 mol / L sodium hydroxide solution was added dropwise under continuous stirring to adjust the pH value to 5.0. The temperature was controlled at 40°C for precipitation reaction for 10 hours. Dark green flocculent precipitates were produced in the reaction liquid. The solid product was filtered to obtain the solid product. The solid product was washed with deionized water and ethanol, dried at 80°C, and crushed to obtain VO(OH)2 powder.

[0068] (2) Preparation of precursor

[0069] Using diammonium hydrogen phosphate as the phosphorus source, sodium carbonate as the sodium source, and glucose as the carbon source, the molar ratio of vanadium oxyhydroxide, phosphorus source, and sodium source is 2:3:3, and the mass ratio of vanadium oxyhydroxide and carbon source is 1:0.5. Amorphous vanadium oxyhydroxide, phosphorus source, sodium source, and carbon source are weighed separately, mixed, and ball milled at a speed of 500 r / min for 7 hours to obtain a precursor.

[0070] (3) Calcination

[0071] The precursor was calcined at 650°C for 10 h and cooled to obtain Na3V2(PO4)3 material.

[0072] Example 8

[0073] The phase-change-free preparation method of the sodium vanadium phosphate material of this embodiment is as follows:

[0074] (1) Preparation of vanadium oxyhydroxide

[0075] According to the molar ratio of vanadium to sodium hydroxide being 1:2, a mixture of vanadium pentoxide and vanadium trioxide in a mass ratio of 1:1 was weighed and added into deionized water, and ultrasonic dispersion was performed uniformly to prepare a vanadium-containing solution with a concentration of 8 g / L, and polyvinyl pyrrolidone was added as a structure directing agent, and the amount of polyvinyl pyrrolidone was 0.001 times the mass of vanadium pentoxide. Then, 0.5 mol / L sodium hydroxide solution was added dropwise under continuous stirring to adjust the pH value to 4.5, and the temperature was controlled at 90°C for precipitation reaction for 1 hour. When dark green flocculent precipitate was produced in the reaction liquid, the solid product was filtered to obtain the solid product, and the solid product was washed with deionized water and ethanol, dried at 80°C, and crushed to obtain VO(OH)2 powder.

[0076] (2) Preparation of precursor

[0077] Sodium dihydrogen phosphate was used as both the phosphorus source and the sodium source, cellulose was used as the carbon source, the molar ratio of vanadium oxyhydroxide, phosphorus source and sodium source was 2:3:3, and the mass ratio of vanadium oxyhydroxide and carbon source was 1:0.4. Amorphous vanadium oxyhydroxide, phosphorus source, sodium source and carbon source were weighed separately and mixed, and ball milled at 600 r / min for 5 h to obtain a precursor.

[0078] (3) Calcination

[0079] The precursor was calcined at 750°C for 8 hours and cooled to obtain Na3V2(PO4)3 material.

[0080] Performance Testing:

[0081] (1) Using Cu target Kα radiation, tube voltage and current of 40 kV and 40 mA respectively, in the range of 10-80°C, X-ray diffraction analysis was performed on the precursor in Example 1 and the Na3V2(PO4)3 materials prepared in Examples 2-5. The results are shown in Figure 2 . Figure 2 The data show that the precursor prepared using non-crystalline vanadium oxyhydroxide as the vanadium source undergoes almost no fusion and transformation of multiple phases during the subsequent calcination process.

[0082] (2) The Na3V2(PO4)3 materials prepared in Example 1 and Comparative Example 1 were used as samples for X-ray diffraction analysis. The results are shown in Figure 3 . Figure 3 The data show that the XRD spectrum of the Na3V2(PO4)3 material obtained after calcination of a precursor prepared by using non-crystalline vanadium oxyhydroxide as a vanadium source has almost no diffraction peaks of the impurity phase, and the product purity is relatively high.

[0083] (3) The Na3V2(PO4)3 materials prepared in Example 1 and Comparative Example 1 were used as samples, as active materials of positive electrode materials of batteries, and mixed with acetylene carbon black and polyvinylidene fluoride in a ratio of 8:1:1 in 1.4 mL N-methylpyrrolidone and solvent, and then placed in a ball mill, and the slurry obtained by unidirectional ball milling for four hours was coated on carbon-coated aluminum foil, dried at 45°C for four hours, and vacuum dried at 120°C for 6 hours. The samples were used as positive electrodes, metallic sodium was used as negative electrodes, and ceramic Celgard diaphragms were used as diaphragms. The electrolyte consisted of NaClO4+EC / DEC+5%FEC; wherein NaClO4, EC, DEC and FEC respectively represent sodium perchlorate, ethylene carbonate, diethyl carbonate and fluoroethylene carbonate; 1M NaClO4 was dissolved in an EC / DEC system with a volume ratio of 1:1, and 5wt% FEC was added to prepare the samples, and button batteries were assembled in a vacuum glove box. Rate performance tests and cycle stability tests were performed. Figure 4The rate performance diagrams of the Na3V2(PO4)3 materials prepared in Example 1 and Comparative Example 1 respectively applied to batteries; Figure 5 These are the cycle stability diagrams of the Na3V2(PO4)3 materials prepared in Example 1 and Comparative Example 1 when used in batteries respectively. Figure 4 The materials prepared in Example 1 and Comparative Example 1 were respectively applied to batteries. Please refer to Table 1 for the discharge specific capacities at different rates.

[0084]

[0085] Figure 4 The data show that when the material of Example 1 is used in a battery, the discharge capacity can reach 117 mAh / g at a circuit density of 1C, and at a high rate of 5C, the discharge capacity of the material of Example 1 can also reach 110 mAh / g, indicating that the material of Example 1 has excellent rate performance. Figure 5 The data show that the initial capacity of Example 1 at 1C is 118 mAh / g, while that of Comparative Example 1 is only 104 mAh / g. After 300 cycles, the discharge capacity of Example 1 is still 110 mAh / g, and the capacity retention rate is 93%, while the capacity of Comparative Example 1 is only 79 mAh / g, and the capacity retention rate is 76%, which is significantly lower than that of Example 1. It can be seen that the discharge capacity of Example 1 is better than that of Comparative Example 1. Figure 4 and Figure 5 The data show that the Na3V2(PO4)3 material of Example 1 has good electrochemical performance when used in batteries.

[0086] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention. The techniques, shapes, and structural parts not described in detail in the present invention are all known technologies.

Claims

1. A method for preparing sodium vanadium phosphate material without phase change, characterized in that: The following steps are involved: Weighing non-crystalline vanadium oxyhydroxide, phosphorus source, sodium source and carbon source respectively, mixing and ball milling for 1 to 7 hours to obtain a precursor; The precursor is calcined at 600-1000°C for 6-10 hours, cooled, and Na3V2(PO4)3 material is obtained.

2. The method for preparing sodium vanadium phosphate material without phase change according to claim 1, characterized in that: The preparation method of the non-crystalline vanadium oxyhydroxide is as follows: Take the vanadium-containing solution, add sodium hydroxide solution under stirring to adjust the pH value to 4.5-5, control the temperature to 40-90°C for precipitation reaction for 1-10 hours, filter to obtain a solid product, wash the solid product with deionized water and ethanol, dry and crush to obtain VO(OH)2 powder.

3. The method for preparing sodium vanadium phosphate material without phase change according to claim 1, characterized in that: The molar ratio of vanadium to sodium hydroxide in the vanadium-containing solution is 1:

2.

4. The method for preparing sodium vanadium phosphate material without phase change according to claim 3, characterized in that: The vanadium-containing solution is an aqueous solution containing a vanadium compound at a concentration of 5 to 10 g / L, and the vanadium-containing compound is at least one of ammonium metavanadate, sodium metavanadate, vanadium pentoxide, vanadium trioxide, and vanadium dioxide.

5. The method for preparing sodium vanadium phosphate material without phase change according to claim 4, characterized in that: The concentration of the sodium hydroxide solution is 0.3-0.6 mol / L.

6. The method for preparing sodium vanadium phosphate material without phase change according to claim 1, characterized in that: The molar ratio of the vanadium oxyhydroxide, the phosphorus source and the sodium source is 2:3:

3.

7. The method for preparing sodium vanadium phosphate material without phase change according to claim 6, characterized in that: The mass ratio of the vanadium oxyhydroxide to the carbon source is 1:(0.2-0.5).

8. The method for preparing sodium vanadium phosphate material without phase change according to claim 7, characterized in that: The phosphorus source is at least one of diammonium phosphate, sodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, diammonium hydrogen phosphate, and phosphoric acid.

9. The method for preparing sodium vanadium phosphate material without phase change according to claim 7, characterized in that: The sodium source is at least one of sodium hydroxide, sodium carbonate, sodium oxalate, sodium dihydrogen phosphate, sodium acetate and sodium citrate.

10. The method for preparing sodium vanadium phosphate material without phase change according to claim 7, characterized in that: The carbon source is at least one of glucose, sucrose, cellulose, starch, carbon nanotubes, acetylene black and graphite.

Citation Information

Patent Citations

  • Preparation method of sodium vanadium phosphate material

    CN114572957A

  • Sodium vanadium phosphate, sodium vanadium manganese phosphate and preparation method thereof

    CN115304046A

  • Vanadium oxygen hydrate based cathodes

    US20210399285A1